Morphometric of Mole Crabs (Anomura: Hippidae) from Ambon Island, Indonesia - Hasan Tuaputty; Fredy Leiwakabessy; Alwi Smith; Eifan Boyke Pattiasina; Muhammad Tarmizi Kubangun (Program Studi Pendidikan Biologi FKIP Unpatti, 2026)
In Maluku, mole crabs are only used as food ingredients by a small number of coastal communities. In Seilale Village, Nusaniwe District, Ambon Island, mole crabs (called